Pharmacophore Based Design of Probable FGFR-1 Inhibitors from the 3D Crystal Structure of Infigratinib - A Drug Used in the Treatment of Cholangiocarcinomas - Sarker, Koushik; Ghosh, Avijit; Saha, Abhijit; Mishra, Suvasish; Sen, Subrata (Letters in Drug Design & Discovery, 2022)
Background: Pemigatinib (INCB054828) and Infigratinib (BGJ398) are the few selective drugs that are approved by the FDA to treat cholangiocarcinoma, a rare form of bile duct cancer. Infigratinib is a pan FGFR inhibitor and has been found promising in Phase-3, first-line PROOF clinical trial. So, screening drug-like compounds having similar pharmacophoric features like infigratinib is the inspiration of the present work. Objective: The objective was to identify drug-like compounds with similar pharmacophoric features as in infigratinib. The compounds screened through the 3D query pharmacophore of infigratinib were also predicted for ADMET properties so that the compounds may have good bioavailability. Methods: A pharmacophore was generated from the crystal structure of infigratinib with several pharmacophoric features such as hydrogen bond donor, hydrophobic, positive ionizable, and ring aromatic. MayBridge database containing 65,263 compounds was used for virtual screening (VS) using LibDock. The initial Hit compounds were subjected to ADMET predictions. Finally, two Hit compounds were selected and docked with the FGFR-1 receptor to predict the interaction of the ligand atoms with the amino acid residues of the receptor's active site. Results: The fit score for infigratinib, N-(4-fluorophenyl)-2-(5-((2-(4-methoxy-2,5-dimethylphenyl)-2- oxoethyl)thio)-4-methyl-4H-1,2,4-triazol-3-yl)acetamide (Hit-1) and 4-(4-((2-(5,6-dimethyl-1H-benzo[d] imidazol-2-yl)ethyl)carbamoyl)pyridin-2-yl)-1-methylpiperazin-1-ium (Hit-4) is 4.58901, 4.36649, and 3.71732, respectively. The LibDock score of infigratinib, Hit-1, and Hit-4 is 122.474, 123.289, and 123.353, respectively. The binding affinity score (-PLP1) of infigratinib, Hit-1, and Hit-4 is -143.19, - 102.72, and -91.71. Conclusion: The present study concluded that the two compounds designated as Hit-1 and Hit-4 have been identified as binders of FGFR-1, and Hit-4 occupies the whole pharmacophoric space of infigratinib, and both the compounds LibDock scores are better than the infigratinib. The two compounds Hit-1 and Hit-4 may be synthesized and studied for their enzyme inhibition assay on FGFR-1 and biologically evaluated on different cell lines for Cholangiocarcinoma.
Keywords: infigratinib